The Investigation Of Translation Shifts In “Monster Pets: A Hotel Transylvania Short Film” - Muhammad Rayhan Ramadhan; Nurma Dhona Handayani (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This research identified the types of translation shifts in “Monster Pets: A Hotel Transylvania Short Film”. Qualitative research was employed as the research design. The data were collected using the observational method by (Sudaryanto, 2015) where the researchers closely observed and compared the original and translated versions of